Accountability and the European Parliament Elections: the Illusion of Supranational Accountability - Kobielska, Katarzyna (Political Preferences, 2014)
The paper refers to the essential problem of the European political space, namely the insufficient implementation scale of accountability standards, which has a direct effect on the democratization of the European political system, spe- cifically on the democracy deficit. The paper was presented the accountability standard on the background on the EP election in 2014, with the strong focus on the relations between the voters and the EP candidates. In the analyses the factors characterizing the quality of political discourse were considered taking into ac- count both, the electorate political activity (principal - in the meaning Principal- Agent-Theory), as well as the offer of the running politicians (as the agents).